2016
DOI: 10.1104/pp.16.00788
|View full text |Cite
|
Sign up to set email alerts
|

SPIKE1 Activates ROP GTPase to Modulate Petal Growth and Shape

Abstract: Plant organ growth and final shape rely on cell proliferation and, particularly, on cell expansion that largely determines the visible growth of plant organs. Arabidopsis (Arabidopsis thaliana) petals serve as an excellent model for dissecting the coordinated regulation of patterns of cell expansion and organ growth, but the molecular signaling mechanisms underlying this regulation remain largely unknown. Here, we demonstrate that during the late petal development stages, SPIKE1 (SPK1), encoding a guanine nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 67 publications
3
38
0
Order By: Relevance
“…The interdigitation of the cells is compromised in the spk1 mutant and in the rop2 rop6 rop4RNAi mutant, and cells display transverse MT arrays. Furthermore, the levels of active ROP2 and ROP6 are lower in spk1 than in wild-type plants (Ren et al, 2016). Taken together, these results indicated that SPK1 is responsible for activating ROP2, ROP6, and likely ROP4, which together regulate the growth of petal epidermal cells.…”
Section: Rop Function During Diffuse Growthsupporting
confidence: 55%
“…The interdigitation of the cells is compromised in the spk1 mutant and in the rop2 rop6 rop4RNAi mutant, and cells display transverse MT arrays. Furthermore, the levels of active ROP2 and ROP6 are lower in spk1 than in wild-type plants (Ren et al, 2016). Taken together, these results indicated that SPK1 is responsible for activating ROP2, ROP6, and likely ROP4, which together regulate the growth of petal epidermal cells.…”
Section: Rop Function During Diffuse Growthsupporting
confidence: 55%
“…To show directly that ROP2 induces TOR signaling activation in response to auxin treatment, we depleted ROPs 2, 4, and 6 ( Fig 3A and B; Ren et al, 2016). First, we found that knockout of only ROP2 substantially reduces the level of ROPs immunoprecipitated by TOR to levels similar to that observed in rop2 rop6 and rop2 rop6 ROP4 RNAi plants, strongly suggesting that ROP2 plays a pivotal role in TOR association ( Fig 3C).…”
Section: Tor Is Up-regulated In Plants With Elevated Levels Of Gtp-bomentioning
confidence: 63%
“…We therefore investigated the role of SPK1 during conical cell development by analyzing the spk1-4 mutant, which was predicted to have aberrant messenger RNA splicing [50]. Our results showed that the spk1-4 mutant also displayed swollen apexes of conical cells (Fig 3), as observed in the rop multiple mutants.…”
Section: Resultsmentioning
confidence: 96%